The effect of dose and time in sowing of rice straw ash to growth and yield sweet potato (Ipomoea batatas L.) - gusti handayani; jonatan ginting (Universitas Sumatera Utara, 2016)
Sweet potato is a high economy value commodity and bring a lot of benefits, In addition to having carbohydrate content high have also containing nutrients helpful for health. The research carried out in agricultural land village Serapuh in June to September 2015, Used randomized block design with two factors that is doses rice straw asher (10g, 20g, 30g, 40g) and time in sowing of a rice straw asher (two weeks before planting , one week before planting, when planting) parameter examined is long branches main, how many branches of, the number of bulb per sample, fresh weight bulb per sample, the dried bulb weight per sample, the number of bulb per a plot, fresh weight bulb per a plot.The result of research showed dose of rice straw ash nothing significantly to all parameter. Time of sowing of rice straw asher significantly of parameter number of branches of 5 and 7 MST. Interaction are significantly on the parameter of fresh bulb weight per sample. The best result of the research is dose of rice straw ash 40g and application of rice straw ash one week before planting. Keywords: rice straw asher, time in swing, sweet potato.